ATTEMPTS TO CONTROL ZOONOTIC CUTANEOUS LEISHMANIASIS - MA . Seyedi -Rashti; A.Nadim (Tehran University of Medical Sciences, 1973)
In 5 villages in Isfahan area, with a population of 1368, rodents were successfully controlled using poisened bait with Zinc phospheid, with 300 meters of houses and built up area. In another 5 villages with a population of 1471, rodent burrows were dusted with DDT within the same distance, without any effect on sandflies. A third group of 5 villages was kept as control. The incidence of cutaneous leishmaniasis was almost the same in these three groups of villages, although rodent control was very effective. This shows that either the flight of sandflies was more than 300 meters of there are other important factors affecting the transmission.